Relationship between Muscle Tone of the Erector Spinae and the Concave and Convex Sides of Spinal Curvature in Low-Grade Scoliosis among Children - Jacek Wilczyński (MDPI AG, 2021)
The objective of the present research was to assess the relationship between muscle tone of the erector spinae and the concave and convex sides of spinal curvature in low-grade scoliosis found among children. The study included 251 children, aged 7-8. Examination of the spine and body posture was carried out using the Diers Formetric III 4D optoelectronic method. Surface electromyography (sEMG) was used to assess erector spinae muscle tone. The trial was carried out using the 14-channel Noraxon TeleMyo DTS apparatus. The highest generalised tone (sEMG amplitude) of the erector spinae occurred in the case of scoliosis. The higher the angle of curvature, the greater the erector spinae muscle tone. Regardless of the position adopted during examination of the thoracic spine, greater erector spinae tone (sEMG amplitude) was exhibited on the convex side of the spinal curvature. However, in the area of the lumbar spine, greater tone (sEMG amplitude) of the erector spinae occurred on the curvature's concave side. The exception was the test performed in a standing position, during which greater muscle tone was noted on the side of the convex curvature. In therapeutic practice, within the thoracic section, too tense erector spinae muscles should be stretched on the convex side of the scoliosis, while in the lumbar region, this should be performed on the concave side. However, each case of scoliosis requires individually tailored treatment. The current research has applicative value and does fill a research gap with regard to erector spinae muscle tone in young children experiencing low-grade scoliosis. The development of scoliosis is associated with asymmetry and an increase in erector spinae tone. The uneven distribution of its tone, occurring on both sides of the spine and in its various segments, causes destabilisation and its abnormal progression.